Bled Dry : a Novel. - Hamdouchi, Abdelilah (Hoopoe Fiction., 2017)
When an ill-fated, young prostitute and her lover are killed in a gruesome double murder, seasoned investigator Detective Hanash is called in. The case draws him and his team into the poverty of Casablanca's slums, blighted by criminality, religious extremism, and despair. Hanash's years on the job have made him intimately familiar with the city's seedy underbelly, but this time he harbors a personal connection to one of the victims, one he must conceal at all costs.